2015
DOI: 10.1055/s-0035-1560318
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Deconjugative Electrophilic Fluorination/Cross-Metathesis: Toward the Synthesis of Fluoro Analogues of Biologically Active Compounds

Abstract: General Methods and Materials 2 General Procedure for α-fluoro-β,γ-unsaturated amides 2 Procedure for Dehydroxyfluorination of α-hydroxy-β,γ-unsaturated 2 Procedure for cross metathesis of allylic fluoride 2 Characterization of the Products 2-9 NMR Spectra of Products 10-Experimental Section General Methods and Materials All reactions were conducted under an argon atmosphere and oven flamed glassware was used. Methylene chloride was distilled over calcium hydride under a nitrogen atmosphere. All other solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…One example reports the use of a platinum catalyst in an allylic substitution reaction with an amine of a non‐functionalized allyl fluoride . Recently, we have developed a rapid process for access to functionalized α‐fluoroenamides from γ‐silylenamides . Herein, we disclose an efficient strategy for the synthesis of a variety of γ‐amino‐α,β‐unsaturated amides from readily available α‐fluoroenamide precursors through an intermolecular conjugative catalytic amination process.…”
Section: Introductionmentioning
confidence: 99%
“…One example reports the use of a platinum catalyst in an allylic substitution reaction with an amine of a non‐functionalized allyl fluoride . Recently, we have developed a rapid process for access to functionalized α‐fluoroenamides from γ‐silylenamides . Herein, we disclose an efficient strategy for the synthesis of a variety of γ‐amino‐α,β‐unsaturated amides from readily available α‐fluoroenamide precursors through an intermolecular conjugative catalytic amination process.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, β-trifluoromethyl-α,β-unsaturated nitrones, ketones, and esters are readily available for various organic transformations for the creation of C–C bonds such as Michael additions (Scheme A), Diels–Alder reactions, Friedel–Crafts reactions, metal-mediated conjugate additions, and other transformations. Recently, from silylamide type A and a cationic fluorine F + source (Selectfluor), we synthesized allylfluoride amides type B , which proved to be very good allylic systems in catalytic allylic substitution processes using different metals (Rh, Ir, Pt) combined with hard or soft nucleophiles (Scheme B) . During this work, we showed that the amide function displays an important role through its metal coordination effect.…”
mentioning
confidence: 98%